Impact Resistance Behaviour of Banana Fiber Reinforced Slabs - Muda Z.C.; Syamsir A.; Mustapha K.N.; Samsudin M.R.; Thiruchelvam S.; Usman F.; Beddu S.; Mohd Kamal N.L.; Alam M.A.; Birima A.H.; Zaroog O.S. (Institute of Physics Publishing, 2023)
Drops; Fruits; Reinforcement; Banana fibers; Banana fibres; Crack resistance; Drop weight impact; Linear relationships; Projectile tests; Slab thickness; Steel balls; Cracks; crack; experimental design; impact; performance assessment; reinforcement; research work; spacing; steel structure; weight